CLINICAL COURSE CHARACTERISTICS OF CHICKENPOX (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper presents a comparative analysis of chickenpox incidence and clinical course in 290 patients hospitalized in the Bukhara Regional Infectious Diseases Hospital during 2023-2024. It was found that children aged 3 to 14years were significantly more likely to be hospitalized, while adults aged 18 to 34 years were more frequently affected (1.3). Neurological signs of chickenpox showed no significant difference between children and adults. The rash in children was localized primarily on the trunk and extremities, while in adults, it was localized on the face and trunk (2). Children exhibited lower intensity of pruritus and less frequent enanthem in mucous membranes compared to adults. Lymphadenopathy in children was more generalized but less frequent in those over 18 years of age. The duration of intoxication syndrome and hospitalization did not significantly differ between children and adults (4).